"Liquid‐To‐Solid" Conversion of Biomass Wastes Enhanced by Uniform Nitrogen Doping for the Preparation of High‐Value‐Added Carbon Materials for Energy Storage with Superior Characteristics. Issue 8 (17th March 2023) - Chernysheva, Daria V.; Sidash, Ekaterina A.; Konstantinov, Maksim S.; Klushin, Victor A.; Tokarev, Denis V.; Andreeva, Veronica E.; Kolesnikov, Evgeny A.; Kaichev, Vasily V.; Smirnova, Nina V.; Ananikov, Valentine P.
Abstract: Sustainable human development urgently calls for decreasing the cost of energy storage. Continuous massive consumption of dedicated carbon electrode materials with complex internal molecular architectures requires rethinking both the source of materials and the process of their production. Finding an efficient sustainable solution is focused on the reuse and development of waste processing into corresponding high‐value‐added carbon materials. The processing of solid wastes into solid value‐added carbon materials ("solid‐to‐solid") is relatively well developed but can be a two‐stage process involving carbon architecture rearrangement and heteroatom doping. Processing liquid wastes into high‐value‐added solid material ("liquid‐to‐solid") is typically much more challenging with the need for different production equipment. In the present study, a new approach is developed to bypass the difficulty in the "liquid‐to‐solid" conversion and simultaneously built in the ability for heteroatom doping within one production stage. Polycondensation of liquid humins waste with melamine (as a nitrogen‐containing cross‐linking component) results in solidification with preferential C and N atomic arrangements. For subsequent thermochemical conversion of the obtained solidified wastes, complicated equipment is no longer required, and under simple process conditions, carbon materials for energy storage with superior characteristics were obtained. A complete sequence is reported in the present study, including liquid waste processing, nitrogen incorporation, carbon material production, structural study of the obtained materials, detailed electrochemical evaluation and real supercapacitor device manufacture and testing. Abstract : Humin nature : Processing liquid wastes into high‐value‐added solid material is challenging and typically requires specialized production equipment. Polycondensation of liquid humins waste with melamine results in solidification with preferential C and N atomic arrangements. Carbon materials for energy storage with superior characteristics are obtained by thermochemical conversion of the obtained solidified wastes under simple process conditions.